The Moderating Effect of Mindfulness on the Mediated Relation Between Critical Thinking and Psychological Distress via Cognitive Distortions Among Adolescents - Su, Michael Ronald; Shum, Kathy Kar-man (Frontiers in Psychology, 2019)
Critical thinking has been widely regarded as an indispensable cognitive skill in the 21st century. However, its associations with the affective aspects of psychological functioning are not well understood. This study explored the interrelations between trait mindfulness, critical thinking, cognitive distortions, and psychological distress using a moderated mediation model. The sample comprised 287 senior secondary school students (57% male, 43% female) aged 14 to 19 from a local secondary school in Hong Kong. The results revealed that high critical thinking was significantly associated with high levels of psychological distress when mindful awareness was low among adolescents. Trait mindfulness was found to moderate the indirect effects of critical thinking on psychological distress via cognitive distortions as the mediator. Specifically, in low trait mindfulness conditions, critical thinking was found to associate positively with cognitive distortions and psychological distress. Such associations were not observed in high trait mindfulness conditions. The findings reveal that though critical thinking has positive associations with cognitive functioning, its associations with affective well-being might be negative. The results also suggest that mindfulness might play an important role in preventing the possible psychological distress associated with critical thinking. Educational implications relating to the fostering of critical thinking and mindful awareness are discussed.